Effect of NaOH Soaking Time on The Thermal Conductivity and Strength Physical Properties Performance of The EFB Cement Board - Abu Soid, Nawal Syahirah; Samsudin, Emedya Murniwaty (Recent Trends in Civil Engineering and Built Environment, 2023)
Chemical treatment using sodium hydroxide (NaOH) becomes the most popular fiber pre-treatment used by many researchers. NaOH treatment on fiber however caused several drawbacks to the physical properties and the fiber’s performance. The objectives of this research are to study the effect of EFB fiber on different NaOH concentrations and soaking time on the tensile strength and determine and compare the EFB cement board thermal conductivity based on different NaOH concentrations and soaking time. This was done by using various NaOH concentrations of 0 %, 1%, 3%, and 5%, percent with a preset soaking time of 1 and 3 hours. The ratio that been apply to the cement board is 3:1 (Fiber:Cement) and the cement board specification size is 150 ×150 × 13 mm for thermal conductivity test. Result on tensile strength of fiber shown that fiber with 5% concentration with 3 hour soaking time has the higher value that can bearing tensile loads. Thus, for thermal conductivity result shown cement board with EFB concentration 5% and 1 hour shown 0.00384 W/mᵒC. of thermal conductivity and is suitable to be used as a thermal insulator. Hence, it can be concluded that the concentration and soaking time of EFB fiber in NaOH during pretreatment gave significant effects to the strength of the strand and thermal conductivity of EFB cement board.